Environmental ratification moves - Pierre Mazzega; Pierre Mazzega; Pierre Mazzega (Frontiers in Political Science, 2024)
For over 60 years, International Environmental Law has produced hundreds of texts aimed at protecting the environment at global to regional scales. Most of these texts do not gather the support of all the states concerned. The reasons for this are analysed here. This retrospective look provides a striking panorama of the current situation. The international and domestic motivations that lead a state to the sovereign decision to ratify or not a treaty, are first recalled and put into perspective in their interdependencies. The analysis of thousands of ratifications of 51 major treaties draws lines of divergence between leading states, follower states, and states reluctant to enter into environmental commitments. On a global scale the latter form a large majority, including most African and Asian states. The states of Northern and Western Europe are among the first to ratify these treaties, followed by other European states. G7 member states occupy vey contrasting normative positions. Overall, three major moves emerge from this global panorama. First, historical and persistent inequalities in the development of countries have cast an indelible shadow on environmental international multilateral treaties which do not bring the expected fruits of development. Second, in environmental matters, over the past 15 years the trend consists in establishing agreements of more restricted range (regional, bilateral), with commitments from states on fairly flexible objectives, adaptable to their social and economic context. Third, these agreements are set within the broadly negotiated and thematically inclusive principles of sustainable development.